The Emerging Role of Gβ Subunits in Human Genetic Diseases - Malerba, Natascia (Cells, 2019)
Environmental stimuli are perceived and transduced inside the cell through the activation of signaling pathways. One common type of cell signaling transduction network is initiated by G-proteins. G-proteins are activated by G-protein-coupled receptors (GPCRs) and transmit signals from hormones, neurotransmitters, and other signaling factors, thus controlling a number of biological processes that include synaptic transmission, visual photoreception, hormone and growth factors release, regulation of cell contraction and migration, as well as cell growth and differentiation. G-proteins mainly act as heterotrimeric complexes, composed of alpha, beta, and gamma subunits. In the last few years, whole exome sequencing and biochemical studies have shown causality of disease-causing variants in genes encoding G-proteins and human genetic diseases. This review focuses on the G-protein β subunits and their emerging role in the etiology of genetically inherited rare diseases in humans.